Computer-Assisted Navigation Is Associated With Decreased Rates of Hardware-Related Revision After Instrumented Posterior Lumbar Fusion. Issue 4 (May 2023) - Bovonratwet, Patawut; Gu, Alex; Chen, Aaron Z.; Samuel, Andre M.; Vaishnav, Avani S.; Sheha, Evan D.; Gang, Catherine H.; Qureshi, Sheeraz A.
Study Design: Retrospective cohort study. Objective: To (1) define utilization trends for navigated instrumented posterior lumbar fusion (PLF), (2) compare reasons and rates of revision at 30-day, 60-day, 90-day, and 1-year follow-up, and (3) compare 90-day perioperative complications between navigated versus conventional instrumented PLF. Methods: Patients who underwent navigated or conventional instrumented PLF were identified from the Humana insurance database using the PearlDiver Patient Records between 2007-2017. Usage of navigation was characterized. Patient demographics and operative characteristics (number of levels fused, interbody usage) were compared between the 2 treatment groups. Propensity score matching was done and comparisons were made for revision rates at different follow-up periods (categorized by reasons) and other 90-day perioperative complications. Results: This study included 1, 648 navigated and 23 429 conventional instrumented PLF. Navigated cases increased over the years studied to approximately 10% in 2017. Statistical analysis after propensity score matching revealed significantly lower rates of hardware-related revision at 90-day follow-up in the navigated cohort (0.49% versus 1.15%, P = .033). At 1-year follow-up, the navigated cohort continued to have significantly lower rates of hardware-related revision (1.70% versus 2.73%, P = .044) as well as all cause revision (2.67% versus 4.00%, P = .032). There were no statistical differences between the 2 cohorts in any of the 90-day perioperative complications studied, such as cellulitis and blood transfusion ( P > .05 for all). Conclusions: These findings suggest that navigation is associated with reductions in hardware-related revisions after instrumented PLF. However, these results should be interpreted cautiously in the setting of potential confounding by other unmeasured variables.